New data on neotectonic contractional structures in Precordillera, south of Río de La Flecha: Structural setting from gravity and magnetic data. San Juan, Argentina - Perucca, Laura Patricia A. (2014)
The Central and Eastern Precordillera form oppositely verging thrust systems on the western and eastern sides of the Matagusanos-Maradona-Acequión valley, establishing a thick-skinned triangle zone with significant changes in the axis position along strike. Between the del Agua and the de La Fecha rivers, the axis of this triangular zone is located in the eastern portion of the depression. Changes in the position of the triangle zone axis along strike, whether to the east or to the west, took place during Pliocene–Pleistocene times. Geophysical and geodetic data indicate a subsurface structure striking NE, oblique to the general direction of the foreland with dextral displacement. Accordingly, the change in the location of the triangular area could be attributed to stress transfer controlled by heterogeneities in the basement. By analytic signal analysis of magnetic anomalies, it is possible to assess the regional structural coupling between Pie de Palo and Eastern Precordillera. The oblique arrangement of basement blocks could explain transverse lineaments and the sigmoidal geometry of the Eastern Precordillera. Geophysical and geological evidence shows that the depression is crossed by several E–W strike-slip faults. These faults possibly controlled the position of the triangle zone axis until Neogene–Pleistocene times by transferring displacements and provoking its jump along strike. Basement structures might have also played a primary role in the location of Quaternary faults trending N–S. Finally, the east–west cross-section geophysical model shows the triangular zone, responding to the different controls imposed by the pre-existing basement structures.